2021
DOI: 10.26480/jcleanwas.02.2021.73.77
|View full text |Cite
|
Sign up to set email alerts
|

Soil Conservation Practices in Forest of Nepal

Abstract: Forests play a vital role in Nepalese rural communities, which rely on them for firewood, employment, additional meals, and good health to sustain and improve their lifestyles. It has contributed to the Nepalese farming system. Soil helps in regulating ecological processes like nutrient uptake, decomposition, and water availability in the forest. Nepal’s annual soil loss ranges from 2-105 t ha-1 with 34% water-induced erosion, 60% mass wasting (geological erosion), and 3 % by wind erosion. Forest soil requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This soil has a high swelling capacity and a dispersive property [39]. These characteristics imply that these soils may cause soil degradation, as well as negative environmental and economic consequences [34]. TVRS 1 is better suited to primary forests, production forests, and conservation areas.…”
Section: Discussionmentioning
confidence: 99%
“…This soil has a high swelling capacity and a dispersive property [39]. These characteristics imply that these soils may cause soil degradation, as well as negative environmental and economic consequences [34]. TVRS 1 is better suited to primary forests, production forests, and conservation areas.…”
Section: Discussionmentioning
confidence: 99%
“…While conventional forest management led to a gross loss of forest cover, participatory forestry extends the vegetation cover and reconciles ecological factors. Paudel et al (2021) mentioned that participatory forestry approaches met the objectives of forest conservation on sustainable basis in Nepal. Zheng et al (2008) found that reforestation activities significantly affected plant structure and soil erosion in Southern China's hilly forest area.…”
Section: Introductionmentioning
confidence: 99%
“…3 Soil is an important component of forest and woodland ecosystems because it aids in the regulation of important ecological processes like nutrient intake, decomposition, and water availability. 4 Soil offers the anchoring, water, and nutrients to trees. As leaves and other vegetation die and disintegrate, trees, as well as other plants and vegetation, play a vital role in the production of new soil.…”
Section: Introductionmentioning
confidence: 99%